Pendidikan Karakter Generasi Berkualitas Berlandaskan Tri Hita Karana - Ni Luh Purnamasuari Prapnuwanti; Ni Made Apti Ida Danuwanti (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2022)
Maintaining good relationships in all elements in life requires character education. Character education will lead to a quality generation. Establishing a relationship cannot be separated from Tri Hita Karana. A good and harmonious relationship between Parhyangan (God Almighty), Pawongan (fellow humans) and Palemahan (the surrounding environment). The younger generation must master innovative character and skills in communicating, adapting, possessing independent, social, cultural skills and understanding leadership within themselves. This character emphasizes good and bad behavior towards establishing relationships with these three components (Tri Hita Karana). So on this occasion the researchers put more emphasis on (1) Character Education, (2) Quality Young Generation and (3) Character based on Tri Hita Karana.